2012
DOI: 10.1007/s00251-012-0605-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of HLA associations: the case of medically refractory pediatric acute lymphoblastic leukemia

Abstract: Although studies of HLA and disease now date back some 50 years, a principled understanding of that relationship has been slow to emerge. Here, we examine the associations of three HLA loci with medically refractory pediatric acute lymphoblastic leukemia (pALL) patients in a case–control study involving 2,438 cases and 41,750 controls. An analysis of alleles from the class I loci, HLA-A and HLA-B, and the class II locus DRB1 illuminates a spectrum of extremely significant allelic associations conferring both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…38 The involvement of the HLA molecule as a functional unit in disease susceptibility is therefore dependent on the presence of the immunodominant antigenic peptide. 17,39 Accordingly, heterogeneity by geographic region in the prevalence of certain infectious agents or other relevant exposures may potentially contribute to the variability observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The involvement of the HLA molecule as a functional unit in disease susceptibility is therefore dependent on the presence of the immunodominant antigenic peptide. 17,39 Accordingly, heterogeneity by geographic region in the prevalence of certain infectious agents or other relevant exposures may potentially contribute to the variability observed.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 There are many examples of HLA associations with neoplasms, including Hodgkin lymphoma, 10,11 nasopharyngeal carcinoma, 12 gastric cancer, 13 invasive cervical carcinoma, 14 and childhood leukemia. [15][16][17][18] Specifically, in the United Kingdom Childhood Cancer Study (UKCCS), Taylor et al in 2002 reported a significantly increased risk of childhood ALL associated with presence of the DPB1*02:01 allele, as well as with other rarer alleles that share antigen binding site pocket profiles with the DPB1*02:01 allotype. 18 Further examination of these data as supertypes (a classification based on overlapping peptide binding specificity) showed that childhood ALL risk increased in the presence of DP2 and DP8 supertypes and decreased in the presence of the DP1 supertype.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of the genome-wide approach that can be addressed by the candidate gene studies is the lack of adequate coverage of certain regions of the genome by the currently available genome-wide arrays, including for multi-allelic and non-SNP markers and certain rare variants. An example is in the evaluation of the HLA [73] and killer-cell immunoglobulin-like receptor (KIR) [99] genes. While the hope is that any association with these loci would be captured by tag SNPs within the region [100], their highly multi-allelic nature and a potential involvement of rare alleles may require a focused examination using specialized methods.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, two additional studies showed increased risks associated with HLA-DRB1*04 in an Iranian [72] and European American population [73]. The HLA-DRB1*15 allele was also identified as a risk locus in two studies [74,75].…”
Section: Immune Responsementioning
confidence: 99%
“…[4][5][6][7][8] In medically refractory ALL, which includes patients considered for stem cell transplantation, a spectrum of associations within the HLA complex was recently demonstrated. 9 However, these findings only account for a small proportion of childhood ALL, suggesting that other genetic associations have yet to be uncovered.…”
Section: Introductionmentioning
confidence: 99%